miR-17-92 Cluster Targets Phosphatase and Tensin Homology and Ikaros Family Zinc Finger 4 to Promote T(H)17-mediated Inflammation - Liu, Si-Qi (American Society for Biochemistry and Molecular Biology, 2014)
The miR-17-92 cluster regulates a broad spectrum of biological processes of T cell immunity. This cluster was found to facilitate T cell proliferation, enhance antitumor activities and promote T cell-dependent antibody responses. However, little is known about the role of this miRNA cluster in the development of autoimmune diseases. Multiple sclerosis is a neuro-destructive autoimmune disease caused by the pathogenicity of T(H)17 cells, whose differentiation is tightly controlled by a variety of transcriptional and post-transcriptional regulators. Our study unveils the critical role of miR-17-92 in T(H)17 differentiation: T cell-specific miR-17-92 deficiency reduced T(H)17 differentiation and ameliorated experimental autoimmune encephalomyelitis (EAE) symptoms. We demonstrated that miR-17 and miR-19b are the two miRNAs in this cluster responsible for promoting T(H)17 responses. MiR-19b represses the expression of Phosphatase and Tensin Homology (PTEN), thereby augmenting the PI3K-AKT-mTOR axis essential for proper T(H)17 differentiation. Meanwhile, miR-17 enhances T(H)17 polarization by inhibiting a novel target, Ikaros Family Zinc Finger 4 (IKZF4). By establishing the miR-17-92 cluster as a key driver of T(H)17 responses, our data identify this miRNA cluster as a potential therapeutic target for the clinical intervention of multiple sclerosis.